Psychological time as information: the case of boredom† - Zakay, Dan (Frontiers in Psychology, 2014)
The flow of time is experienced by humans although the exact nature of time is not well understood. The importance of time in human's life is not in dispute and is reflected by several dimensions like duration, which is best representing the naive meaning of time. Psychological time serves seveal important functions which are essential for being able to act and survive in a dynamic environment. In the present paper we argue that psychological time in the form of sensing the pace of the flow of time provides important information to the executive system which control and monitor behavior. When information processing load is below an optimal level for a specific individual, a feeling of boredom is raised. Boredom is accompanied by a slowing of the felt pace of the flow of time. Boredom is a unique mental state which is linked with decreasing efficeincy in cognitive and perceptual performance and is correlated with low job satisfaction and general well-being. As such, boredom poses a threat to normal functioning. We suggest that the felt slowing in the flow of time is a signal which, similarly to pain, is aimed at alerting the executive system that resources should be recruited in order to cope with the hazardous state.